The relationship between the heart-type fatty acid binding protein levels, carotid intima media thickness and epicardial fat thickness in patients with obstructive sleep apnea syndrome - Azar, Cebrail; Abakay, Ozlem; Azar, Sengul; Kermenli, Tayfun; Yuksel, Hatice (Turkish Assoc Tuberculosis & Thorax, 2020)
Introduction: In this study, we aimed to evaluate the relationship between carotid artery intima-media thickness, epicardial fat thickness measurement and the levels of heart-type fatty acid binding protein (hFABP) in patients with obstructive sleep apnea syndrome (OSAS). Materials and Methods: Ninety-nine newly diagnosed OSAS patients and fifty non-OSAS control subjects were enrolled in this study. In both groups, demographic data such as age, sex, body mass index (BMI) were recorded and carotid intima-media thickness (CMIT) and epicardial fat thickness (EFT) were measured. hFABP levels were determined using the enzyme-linked immuno-sorbent assay (EUSA) method according to the manufacturer's protocols. Results: Patients with OSAS 67% male, 33% female gender is determined. The mean age of control group was 43.28 +/- 12.12 years and group of OSAS was 47.85 +/- 11.55 years (p< 0.026). In OSAS group; 38 mild OSAS (38.38%), 23 moderate OSAS (23.23%) and 38 severe OSAS (38.38%) patients were identified. In OSAS patients, average of apnea hypopnea index AHI) was 29.83/hours. A positive correlation was observed between BMI with EFT and CMIT (p< 0.05). hFABP levels in OSAS group average was 2.65 +/- 2.1 ng/mL and in control group average was 1.62 +/- 0.90 ng/mL and this was statistically significant (p= 0.002). EFT, in the control group average was 5.3 +/- 2.04 mm, while the average was 4.3 +/- 1.79 mm in the OSAS group (p= 0.019). The correlation was observed between the CMII and EFT (p< 0.001). I here was no significant difference in BMI and gender between OSAS and control groups. No accompanying cardiovascular disease was detected in patients with OSAS. Conclusion: This study suggests EFT and hFABP can be used as a predictive value in determining cardiovascular risk in OSAS patients.
Obstrüktif uyku apne sendromlu hastalarda kalp tipi yağ asidi bağlayıcı protein düzeyleri, karotis intima media kalınlığı ve epikardiyal yağ kalınlığı arasındaki ilişki
Keywords: Obstructive sleep apnea syndrome; heart type fatty acid binding protein; intima-media thickness; epicardial fat thickness